A conceptual report on meaningful work, perceived organizational support and work engagement among academic staff - Mohsin, Farhana Hanim; Abas, Bahijah; Zainal Adnan, Ahmad Amri (International Journal of Accounting, Finance and Business, 2026)
Academic staff are not only looking for stable employment for their job but also looking for work that can provide meanings and align with their values and how it can benefits others. Recent research has examined the influence of meaningful work and how it leads to higher motivation and engagement, improved retention and other positives work outcomes. Higher learning institutions around the world operate within different educational systems, each of their own are shaped by own policies, economic conditions and contextual relevance. These differences play a major role in shaping the factors that influence academic staff work engagement. This report utilizes the Job Demand-Resources (JD-R) model, which is a critical model for describing how demands and resources interact and forecasting important organisational outcomes. Perceived organizational support (POS) is examined in relation to meaningful work and academic staff’s work engagement. It is proposed that these relationships reflect motivational processes of the JD–R model. This study will construct a viable research agenda based on the review, which will include opportunities for theoretical and empirical findings. As a result, both institutions and scholars may benefit from fostering meaningful work and POS in order to improve work engagement among academic staff.